Analysis of the Needs for a Recording System for Raw Materials and Finished Products at the Om Ending Convection - Nardine Nur Asyifa; Ahmad Ramdani; Sahwa Aninda Kusnandar; Rian Piarna (Expert Net: Exploration Journal of Technological Education Trends, 2026)
This web-based convection information system was developed using the Software Development Life Cycle (SDLC) Waterfall model to address the main issues in manual stock management within convection businesses, including inaccuracies in recording and the risk of loss for both raw materials and finished products. The system is designed to provide an integrated solution, including multi-level user authentication (admin, owner, warehouse staff, and production staff), real-time summary dashboard, management of raw materials, finished products, supporting items, as well as a warehouse module for recording incoming and outgoing goods with early warning for low stock. Its implementation utilizes Native PHP and MySQL database on the XAMPP environment, having undergone requirements analysis through interviews and observations, design of DFD levels 0-3 and ERD, intuitive UI/UX implementation, and manual black-box testing that validates functional accuracy. Overall, the system accelerates the recording process by up to 70%, significantly improves stock data accuracy, and supports strategic decision-making through exportable automatic audit reports, thereby reducing the likelihood of human error in convection business operations. This development not only optimizes the efficiency of textile SMEs like Konveksi Om Ending but also provides a scalable foundation for expansion, including predictive analytics integration and mobile access, ensuring long-term competitiveness in the digital era.